Effect of Intravenous Paracetamol on Opioid Consumption in Multimodal Analgesia After Lumbar Disc Surgery: A Meta-Analysis of Randomized Controlled Trials - Yin, Feng; Wang, Xiu-Hong; Liu, Fei (Frontiers in Pharmacology, 2022)
Background: Intravenous paracetamol as an adjunct to multimodal analgesia has been shown to successfully reduce opioid consumption after joint arthroplasty, abdominal surgery, and caesarean delivery. However, there are limited data on the opioid-sparing effect of intravenous paracetamol on lumbar disc surgery. Objectives To investigate the effectiveness and safety of intravenous paracetamol for reducing opioid consumption in lumbar disc surgery. The primary outcome was cumulative opioid consumption within 24 hours postoperatively. Method: We followed the PRISMA-P guidelines, and used GRADE to assess the quality of evidence. The review was registered in PROSPERO under the registration number CRD42021288168. Two reviewers conducted electronic searches of Pubmed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and Web of Science (Clarivate Analytics). Randomized controlled trials (RCTs) that compared the postoperative opioid consumption of intravenous paracetamol with placebo in lumbar discectomy were included. Results: Five trials comprising a total of 271 patients were included. Overall opioid consumption within 24 hours postoperatively was reduced [mean difference (MD), −10.61 (95% CI, −16.00 to −5.22) mg, P = 0.0001, I2 = 90%] in patients with intravenous paracetamol. Intravenous paracetamol significantly reduced postoperative pain scores at 1 hour [MD, −2.37 (95%CI, −3.81 to −0.94), P = 0.001, I2 = 82%], 2 hours [MD, −3.17 (95%CI, −3.85 to −2.48), P < 0.00001, I2 = 38%], 6 hours [MD, −1.75 (95%CI, −3.10 to −0.40), P = 0.01], 12 hours [MD, −0.96 (95%CI, −1.77 to −0.15), P = 0.02] and 24 hours [MD, −0.97 (95%CI, −1.67 to −0.27), P = 0.006] compared with placebo. There were no differences in postoperative adverse effects. Conclusions: Intravenous paracetamol reduced postoperative opioid consumption and decreased postoperative pain scores without increasing adverse effects. The overall GRADE quality of evidence was rated as low to moderate. Intravenous paracetamol appears to be an applicable option as an important part of multimodal analgesia for postoperative analgesia after lumbar disc surgery.